Generation Z Sharia investment decision patterns: Does information media matter? - Khavid Normasyhuri; Yuli Dahlia Saputri; Erike Anggraeni (Jurnal Ekonomi & Keuangan Islam, 2023)
Purpose – This research examines the relationship between information quality, subjective norms, behavioral control in Generation Z Sharia investment decisions during the Covid-19 era. It also explores how media information can either reinforce or counter these factors.Methodology – Quantitative analysis was conducted in this study using SmartPLS 3.0. Primary data were collected from investor respondents during the Covid-19 pandemic from December 2021 to December 2022. The data collection was facilitated through Google Forms, and the indicator measurement utilized the Likert Scale.Findings – The study revealed a positive relationship pattern between information quality and behavioral control with Islamic investment decision-making in Generation Z during the Covid-19 era. Additionally, subjective norms showed a negative relationship pattern with Sharia investment decision-making in Generation Z during this time. Moreover, information media was found to influence the impact of information quality, subjective norms, and behavioral control on Islamic investment decision-making among Generation Z during the Covid-19 era.Implication – The insights from this research have been shared with investors, serving as a foundational reference for planning and implementing more effective and sustainable Sharia investment programs and strategies.Originality – This study introduces an alternative perspective by focusing on the realm of Islamic investment decisions made by Generation Z, a unique demographic with distinct characteristics, preferences, and behaviors. This investigation was conducted within the context of economic shocks, specifically during the Covid-19 period, and emphasized the role of information media as a crucial channel for rapid access to information, particularly through digital media. Additionally, the study employed the PLS-SEM model, adding a novel methodological approach to the research.